Myeloid/lymphoid neoplasms with eosinophilia and tyrosine kinase gene fusions: reevaluation of the defining characteristics in a registry-based cohort - Metzgeroth, Georgia; Steiner, Laurenz; Naumann, Nicole; Lübke, Johannes; Kreil, Sebastian; Fabarius, Alice; Haferlach, Claudia; Haferlach, Torsten; Hofmann, Wolf-Karsten; Cross, Nicholas C. P.; Schwaab, Juliana; Reiter, Andreas (Leukemia, 2023)
In a registry-based analysis of 135 patients with “myeloid/lymphoid neoplasms with eosinophilia and tyrosine kinase gene fusions” (MLN-TK; FIP1L1::PDGFRA, n = 78; PDGFRB, diverse fusions, n = 26; FGFR1, diverse, n = 9; JAK2, diverse, n = 11; ETV6::ABL1, n = 11), we sought to evaluate the disease-defining characteristics. In 81/135 (60%) evaluable patients, hypereosinophilia (>1.5 × 109/l) was observed in 40/44 (91%) FIP1L1::PDGFRA and 7/7 (100%) ETV6::ABL1 positive patients but only in 13/30 (43%) patients with PDGFRB, FGFR1, and JAK2 fusion genes while 9/30 (30%) patients had no eosinophilia. Monocytosis >1 × 109/l was identified in 27/81 (33%) patients, most frequently in association with hypereosinophilia (23/27, 85%). Overall, a blast phase (BP) was diagnosed in 38/135 (28%) patients (myeloid, 61%; lymphoid, 39%), which was at extramedullary sites in 18 (47%) patients. The comparison between patients with PDGFRA/PDGFRB vs. FGFR1, JAK2, and ETV6::ABL1 fusion genes revealed a similar occurrence of primary BP (17/104, 16% vs. 8/31 26%, p = 0.32), a lower frequency (5/87, 6% vs. 8/23, 35%, p = 0.003) of and a later progression (median 87 vs. 19 months, p = 0.053) into secondary BP, and a better overall survival from diagnosis of BP (17.1 vs. 1.7 years, p < 0.0008). We conclude that hypereosinophilia with or without monocytosis and various phenotypes of BP occur at variable frequencies in MLN-TK.
Online veröffentlicht: 15. Juli 2023
Gesehen am 17.07.2024